2012
DOI: 10.1371/journal.pone.0034506
|View full text |Cite
|
Sign up to set email alerts
|

First Large-Scale DNA Barcoding Assessment of Reptiles in the Biodiversity Hotspot of Madagascar, Based on Newly Designed COI Primers

Abstract: BackgroundDNA barcoding of non-avian reptiles based on the cytochrome oxidase subunit I (COI) gene is still in a very early stage, mainly due to technical problems. Using a newly developed set of reptile-specific primers for COI we present the first comprehensive study targeting the entire reptile fauna of the fourth-largest island in the world, the biodiversity hotspot of Madagascar.Methodology/Principal FindingsRepresentatives of the majority of Madagascan non-avian reptile species (including Squamata and Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
155
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 187 publications
(164 citation statements)
references
References 84 publications
8
155
0
1
Order By: Relevance
“…We do not suggest interpreting mitochondrial non-monophyly of T. gravenhorstii and T. elegans as indicative of these taxa containing cryptic species, given that the multi-gene phylogeny of Lima et al (2013) identified each of these two species as monophyletic, in a multi-gene analysis that included four nuclear genes. In fact, our results highlight the need for caution when relying on pure DNA barcode analysis, as the p-distances calculated between the main subclades of these species (ranging from 6.3-14.5%) are well above the species-level threshold established for scincid species (6.1%, Nagy et al 2012), but it is unlikely that each represents a distinct species.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…We do not suggest interpreting mitochondrial non-monophyly of T. gravenhorstii and T. elegans as indicative of these taxa containing cryptic species, given that the multi-gene phylogeny of Lima et al (2013) identified each of these two species as monophyletic, in a multi-gene analysis that included four nuclear genes. In fact, our results highlight the need for caution when relying on pure DNA barcode analysis, as the p-distances calculated between the main subclades of these species (ranging from 6.3-14.5%) are well above the species-level threshold established for scincid species (6.1%, Nagy et al 2012), but it is unlikely that each represents a distinct species.…”
Section: Resultsmentioning
confidence: 59%
“…We used the reptile-specific primers RepCOI-F (TNT TMT CAA CNA ACC ACA AAG A) and RepCOI-R (ACT TCT GGR TGK CCA AAR AAT CA) of Nagy et al (2012) to amplify a COI fragment of 612 bp. The thermocycling profile comprised an initial denaturation at 94°C for 2:20 min, followed by 35 cycles of denaturation (94°C for 30 s), annealing (45-49°C for 45 s), elongation (72°C for 90 s), and a final elongation step at 72°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 9,084 species of reptiles have been described so far (Uetz, 2010), and new molecular evidence continues to unearth numerous cryptic species that had not previously been detected by morphological analyses (e.g., Adalsteinsson et al, 2009;Nagy et al, 2012;Oliver et al, 2009). Yet as a group, reptiles are currently poorly-represented on the IUCN Red List of Threatened Species, with only 35% of described species evaluated, and those that are evaluated were done so in a non-systematic manner (IUCN, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…To obtain molecular comparisons of the new species with previously unstudied nominal Paroedura species, we sequenced a fragment of the mitochondrial gene for cytochrome oxidase subunit I (cox1) with primers and protocols defined by Nagy et al (2012) for several Paroedura samples from Tsingy de Namoroka (corresponding voucher specimens to be catalogued in MNHN). These samples have become available through a recent herpetological survey by one of us (II) and include topotypical P. karstophila, previously unstudied from a molecular perspective.…”
Section: Methodsmentioning
confidence: 99%
“…These samples have become available through a recent herpetological survey by one of us (II) and include topotypical P. karstophila, previously unstudied from a molecular perspective. The resulting sequences were combined with those of Nagy et al (2012) and Koubová et al (2014) in MEGA version 5 (Tamura et al 2011) to yield an alignment of 664 bp. We performed phylogenetic inference in MEGA under the Maximum Likelihood optimality criterion, with a general time-reversible substitution model with gamma-distributed rates and invariant sites, NNI branch swapping, and assessing robustness of nodes with 500 bootstrap replicates.…”
Section: Methodsmentioning
confidence: 99%